THE FUNCTION OF SLANG USED IN THE FATE AND FURIOUS MOVIE - Ni Made Verayanti Utami; Ni Nyoman Deni Ariyaningsih; Ni Kadek Sinta Sri Nadila (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
The study concerns with the slang word and that occur in the Fate of the Furious Movie. The study aims to analyze the types of slang, the meaning of slang and the function of slang used in Fate of the Furious movie. This study used qualitative approach and the data collection was based on observation method by downloading the movie and movie script, watching the movie, looking through the scene and taking note. The theory used in this study are based on Leech (1981) there are five types of function of language and Chapman (2007) states there are two kind of slang: primary slang and secondary slang. The meanings of slang were taken from some online dictionaries that related to slang. This study reveals that there are 25 slangs which is found in Fate of the Furious movie. From the data, there are 22 primary slangs and 3 secondary slangs found. The meaning of slang mostly related to informational function which is focused on the speaker tends to inform something to the other characters in the movie. From the analysis of the meaning can be concluded that the meaning of slang are various.The study concerns with the slang word and that occur in the Fate of the Furious Movie. The study aims to analyze the types of slang, the meaning of slang and the function of slang used in Fate of the Furious movie. This study used qualitative approach and the data collection was based on observation method by downloading the movie and movie script, watching the movie, looking through the scene and taking note. The theory used in this study are based on Leech (1981) there are five types of function of language and Chapman (2007) states there are two kind of slang: primary slang and secondary slang. The meanings of slang were taken from some online dictionaries that related to slang. This study reveals that there are 25 slangs which is found in Fate of the Furious movie. From the data, there are 22 primary slangs and 3 secondary slangs found. The meaning of slang mostly related to informational function which is focused on the speaker tends to inform something to the other characters in the movie. From the analysis of the meaning can be concluded that the meaning of slang are various.